Profil Antisipasi Siswa Kelas Unggulan MTS Negeri 2 Bondowoso dalam Memecahkan Masalah Bangun Ruang Sisi Lengkung - Irma Suryani (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Anticipation is an important for students in determining the actions to be taken to solve the math problem. Furthermore, for student in superior class. Anticipation is classied into five, namely impulsive anticipation, tenacious anticipation, explorative anticipation, analytic anticipation, and interiozed anticipation. By knowing the anticipation profile of students in superior classes, teachers be able to create conducive learning environment such that students cbe able to optimizing their abilities to solve mathematics problems. This research provides a description of the anticipation profile possessed by superior class students in solving mathematical problems on curved-sided of solid geometric material. The methods used in this research are test and interview methods. The result showed that in superior classes there were three types of anticipation use by students in solving problems, namely analytic anticipation, explorative anticipation, and interiozed anticipation. Based on the fulfillment of anticipation indicators, it could be concluded that superior class IX students 59% use analytic anticipation in solving math problems.
Reupload File Repository_Yudi Approved by Teddy
Keywords: Anticipation; Mathematical Problems; Superior Class; Geometry